2008
DOI: 10.1186/1472-6963-8-266
|View full text |Cite
|
Sign up to set email alerts
|

Provincial prenatal record revision: a multiple case study of evidence-based decision-making at the population-policy level

Abstract: Background: There is a significant gap in the knowledge translation literature related to how research evidence actually contributes to health care decision-making. Decisions around what care to provide at the population (rather than individual) level are particularly complex, involving considerations such as feasibility, cost, and population needs in addition to scientific evidence. One example of decision-making at this "population-policy" level involves what screening questions and intervention guides to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Clinicians face pragmatic realities when they try to include environmental health assessment and counselling in routine clinical practice. Numerous studies in the field of tobacco control have addressed some of these challenges such as those examining brief motivational counselling [ 61 ] or the inclusion of tobacco assessment criteria in standard prenatal records [ 62 , 63 ]. Similar efforts are needed in relation to other environmental hazards.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians face pragmatic realities when they try to include environmental health assessment and counselling in routine clinical practice. Numerous studies in the field of tobacco control have addressed some of these challenges such as those examining brief motivational counselling [ 61 ] or the inclusion of tobacco assessment criteria in standard prenatal records [ 62 , 63 ]. Similar efforts are needed in relation to other environmental hazards.…”
Section: Discussionmentioning
confidence: 99%
“…Research currently underway has revealed that the participants and processes involved in the revision of prenatal record forms vary considerably across Canadian jurisdictions, and the inclusion (or not) of specific prenatal screening questions may be influenced by such diverse factors as feasibility, cost or population needs. 31 More information about contextual factors such as provincial rates of maternal risk drinking and FASD, marketing of alcohol, and the presence or influence of provincial FASD committees is needed to better understand the uptake of research evidence related to screening and interventions for maternal alcohol consumption into provincial/territorial prenatal record forms.…”
Section: Discussionmentioning
confidence: 99%
“…11 To facilitate the transfer of important pregnancy information between members of the circle of care as well as between different health care facilities, Canadian provinces and territories have developed prenatal records. 12 These records help standardize the information both obtained from and delivered to pregnant women and are novel because they illuminate some of the information that is communicated to this vulnerable population. In Canada, each province and territory has its own prenatal record with the exception of the Yukon, which uses the same record as British Columbia.…”
Section: Sources Of Food Safety Information For Pregnant Womenmentioning
confidence: 99%
“…In Canada, each province and territory has its own prenatal record with the exception of the Yukon, which uses the same record as British Columbia. 12 A copy of each of these prenatal records was obtained from government websites, the College of Physicians and Surgeons for that province/territory, or by directly contacting a practicing obstetrician/gynecologist in that province/territory. An excerpt from Alberta's Prenatal Record is shown in Figure 1.…”
Section: Sources Of Food Safety Information For Pregnant Womenmentioning
confidence: 99%